Optimization of radial line slots array antenna design for satellite communications - Iliya, S. Z (2013)
This paper presents a numerical method of identifying the beam squinting optimal design parameters. It is aimed at eradicating the arbitrary method of selection of phi, (phi) thetaT(theta(T)) and phiT(phi(T)) which improves the overall production process. Arbitrary selection of design parameters for beam squinting method which has been identified to solve the inherent return loss problems associated with the linearly polarized radial line slots array (LP-RLSA) design is time wasting and slows satellite design and manufacturing process. Results from the numerical solutions are computed using CST microwave studio (CST 2010); an antenna design software. Simulation results were compared with those obtained from literatures and it showed excellent agreement)